Toxic Effects of Synthesized Bismuth Oxide/Reduced Graphene Oxide (Bi2O3/RGO) Nanocomposites in Two Distinct Mammalian Cell Lines: Role Oxidative Stress and Apoptosis - Lateef R; Ahmad I; Mahdi AA; Lohia N; Alhadlaq HA; Akhtar MJ; Ahamed M (International Journal of Nanomedicine)
Rashid Lateef,1,2 Israr Ahmad,2 Abbas Ali Mahdi,3 Neha Lohia,1 Hisham A Alhadlaq,4 Mohd Javed Akhtar,4 Maqusood Ahamed4 1School of Life and Basic Sciences, Jaipur National University, Jaipur, Rajasthan, 302017, India; 2Department of Biotechnology, Era University, Lucknow, Uttar Pradesh, 226003, India; 3Department of Biochemistry, Era University, Lucknow, Uttar Pradesh, 226003, India; 4King Abdullah Institute for Nanotechnology, King Saud University, Riyadh, 11451, Saudi ArabiaCorrespondence: Maqusood Ahamed, King Abdullah Institute for Nanotechnology, King Saud University, Riyadh, 11451, Saudi Arabia, Email mahamed@ksu.edu.saBackground: Researchers have shown substantial interest in bismuth oxide/reduced graphene oxide (Bi2O3/RGO) nanocomposites due to their superior features that are not achievable by each material alone. The growing applications and manufacturing of Bi2O3/RGO nanocomposites have raised concerns regarding their potential human health risks. This work was designed to explore the possible toxicity mechanisms of Bi2O3/RGO nanocomposites in two distinct mammalian cell lines, normal rat kidney cells (NRK52E) and human liver cancer cells (HepG2).Methods: Bi2O3/RGO nanocomposites were prepared by a simple hydrothermal technique. X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and dynamic light scattering (DLS) were used to characterize the synthesized nanocomposites. The cytotoxicity of Bi2O3/RGO nanocomposites in NRK52E and HepG2 cells was examined by MTT cell viability assay. Reactive oxygen species (ROS) and glutathione (GSH) were measured as the biomarkers of oxidative stress. The apoptosis study was carried out by measuring several parameters, including cell cycle and caspase-3.Results: High-quality Bi2O3/RGO nanocomposites of ≈33– 38 nm size without impurities, where crystalline Bi2O3 particles are evenly attached to the RGO sheets. Bi2O3/RGO nanocomposites exhibit cytotoxic effects on NRK52E and HepG2 cells, which were dose- and time-dependent. Interestingly, NRK52E exhibited marginally higher vulnerability to Bi2O3/RGO nanocomposites compared to HepG2. Bi2O3/RGO nanocomposites also cause a dose-dependent increase in ROS production and a decrease in GSH levels. Exposing NRK52E and HepG2 cells to Bi2O3/RGO nanocomposites results in activation of the caspase-3 enzyme and chromosomal condensation. The apoptotic response of Bi2O3/RGO nanocomposites against both types of cells was further confirmed by AO-EB dual staining and altered cell cycle.Conclusion: This study demonstrated that the toxicity of Bi2O3/RGO nanocomposites in both NRK52E and HepG2 cells is attributed to their ability to produce ROS, leading to apoptosis and cell cycle arrest as a consequence of oxidative stress. Keywords: Bi2O3/RGO nanocomposites, health effects, NRK52E, HepG2, Caspase-3, ROS, apoptosis